O ujęciu przepadku składników i praw majątkowych przedsiębiorstwa w projektowanym art. 44a § 1 kodeksu karnego - Pohl, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article presents my analysis of Polish planned law concerning the confiscation of enterprise’s property. The analysis leads to the conclusion that the regulations are unconstitutional, because they do not respect the constitutional principle that criminal liability is bound to commiting offence.
Keywords: konfiskata mienia; przepadek; odpowiedzialność karna przedsiębiorstwa